×

Sorry!, This page is not available for now to bookmark.

In Mathematics, identity is defined as an equation that holds or valid irrespective of the value chosen for its variables. They are used to simplify or rearrange algebraic expressions. The definition states that two identities are replaceable, so we can replace one identity with another identity at any time. For example, the identity (p + q)² = (p² + q² + 2pq), is true for all the alternatives of p and q, whether they are real or complex numbers.

The identities that are obtained by multiplying one binomial with another binomial is known as standard identities. Read the article below to know more about standard identities.

(Image will be uploaded soon)

Standard identities are identities that are introduced by multiplying one binomial with another binomial.

Example,

let us consider (p+q)(p +q) or (p +q)²

(p + q)² = (p + q)(p + q)

(p + q)(p + q) or (p + q)²

p² + pq + pq + q²

p² + q² + 2pq (as pq = qp)

Hence, (p + q)² = p² + q² + 2pq (1)

Clearly, we can see this is an identity as the expression on LHS is obtained from the RHS. One may verify that for any values of p and q, the values of two sides will always be equal.

Next, we consider, (p - q)(p - q) or (p - q)²

We can say, (p - q)² = (p - q)(p - q)

p(p - q) q(p - q)

p² - pq - pq + q²

p² + q² - 2pq as (pq = qp)

Hence, (p - q)² = p² + q² - 2pq (2)

Next, we consider (p + q)(p - q). We can say, (p + q)(p - q)= p(p - q) + q(p - q)

(p² - pq + pq - q²) = p² - q² (as pq = qp)

(p + q)(p - q) = p² - q² (3)

Finally, we consider (p + q) (p + r) We can say, (p + q) (p + r) = p² + pr + pq + qr

or

(p + q) (p + r) = p² + (q + r)p +pq (4)

The above-given identities 1, 2, 3, 4 are considered as standard identities.

An algebraic identity is an equation that is valid for any value of its variables.

For example, the identity (p + q)² = p² + 2pq + q² is valid for all values of p and q.

As an identity holds valid for all values of its variables, it is possible to replace one side of equality with another side of equality. For example, in the above-given identity, we can easily substitute instances of (p + q)² = p² + q² + 2pq and vice versa.

Using identity in an intelligent way offers shortcuts to many problems by making algebra easier to operate. Below is a list of some standard algebraic identities.

Following are some of the standard identities in Algebra under binomial theorem.

Identity 1: (p + q)² = p² + 2pq + q²

Identity 2: (p - q)² = p² + q² - 2pq

Identity 3: (p + q)³ = p³ + q³ + 3pq(p + q)

Identity 4: (p - q)³ = p³ - q³ - 3pq(p - q)

Identity 5: (p + q)⁴ = p⁴ + 4p³q + 6p²q² + 4pq³ + q⁴

Identity 6: (p - q)⁴ = p⁴ - 4p³q + 6p²q² - 4pq³ + q⁴

Following standard algebraic identities are factoring formula:

Identity 1: p² - q² = ( p + q)(p - q)

Identity 2: p³ + q³ = (p + q)(p² + q² - pq)

Identity 3: p³ - q³ = ( p - q)(p² + q² + pq)

Identity 4: p⁴ - q⁴ = (p² + q²)(p² - q²)

Following standard identities in three- variables are obtained by some factoring and manipulation of terms.

Identity 1: (p + q)(p + r)(q + r) = (p + q + r)(pq + pr +qr) - pqr

Identity 2: p² + q² + r² = (p + q + r)² - 2 (pq + pr + qr)

Identity 3: p + q + r - 3pqr = (p + q + r)(p² + q² + r² - pq - pr - qr)

1. Using identity, (p + q)² = p² + q² + 2pq

Find (2m + 3n)²

Solution:

As we know, (p + q)² = p² + q² + 2pq

Accordingly, (2m + 3n)² = (2m)² + (3n)² + 2(2m)(3n)

Hence, (2m + 3n)² = 4m² + 9n² + 12mn

2. Using identity, (p - q²) = (p² + q² - 2pq)

Find (2m - 3n)²

Solution:

As we know, (p - q²) = (p² + q² - 2pq)

Accordingly, (2m - 3n)² = (2m)² +(3n)² - 2(2m)(3n)

Hence, (2m + 3n)² = 4m² + 9n² - 12mn

3. Using Identity,(p + q)(p - q) = p² - q²

Find (2m + 3n) (2m - 3n)

Solution:

As we know, (p + q)(p - q) = p² - q²

Accordingly, (2m + 3n)(2m - 3n) = (2m)² - (3n)²

(2m + 3n)(2m - 3n) = 4m² - 9n²

FAQ (Frequently Asked Questions)

1. What are the Identities in Mathematics?

Ans: In Mathematics, identities are defined as an equation that is valid irrespective of the values chosen for its variables. Identities are used to simplify or rearrange algebraic expressions. By definition, it states that two sides of identities are interchangeable. Hence, we can replace one with another at any time. For example, (x + y)² = (x² + y² + 2xy) is valid for all alternatives of x and y, whether they are real or complex numbers.

2. How to Learn Algebraic Identities Easily.

Ans:

Algebraic identities can easily be learned by observing the different identities as square or rectangles.

Algebraic identities can also be remembered in the factored form rather than simplified form.

3. Mention the Distinction Between Algebraic Expressions and Identities?

Ans: An algebraic expression is an expression that includes both variables and constant. In algebraic expressions, variables can consider any values. Hence, the values of an expression can be changed if the values of the variable changes. But identities are an equation that are valid for all the values of variables.

4. What is a Binomial Theorem?

Ans: The binomial theorem is an outcome of expanding the powers of binomials or the addition of two terms. The binomial theorem is also referred to as binomial expansion. The coefficients of the term in the binomial expansion are known as binomial coefficients. The binomial theorem and its concepts can be used to prove results and solve problems in combinatorics, algebra, calculus, and many other divisions of mathematics.